The fixed wage puzzle: Why profit sharing is so hard to implement - Jürgen Jerger; Jochen Michaelis (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
It is well known that profit sharing arrangements Pareto-dominate fixed wage contracts. Share agreements are (far) less than ubiquitous, however. This paper offers a solution of this 'fixed wage puzzle' by adopting a perspective of bounded rationality. We show that share arrangements that fulfill 'plausible' constraints are not generally acceptable to both firms and unions.
Keywords: E24; J33; 330; profit sharing; share economy; remuneration systems; Lohnbildung; Erfolgsbeteiligung; Lohnverhandlungen; Beschränkte Rationalität; Theorie